Project-Based Learning Model in Productive Digital Literacy Training - Nunu Mahmud Firdaus; Uyu Wahyudin; Elih Sudiapermana; Yanti Shantini; Simona Sava (Universitas Negeri Semarang, 2026)
Background - The low level of productive digital literacy skills among equality education learners in Community Learning Centers (CLC) has become a major challenge to community empowerment in the digital era. Digital literacy training in CLC is still conventional, lecture-centered, and lacks contextual relevance. Research Urgency - Non-formal education institutions need innovative and participatory learning models to strengthen digital competence and creativity among learners. However, existing digital literacy programs remain limited to basic operational skills and have not yet developed productive digital capabilities. Research Objectives - This study aims to develop a productive digital literacy training model based on Project-Based Learning (PjBL) that is innovative, participatory, and contextually appropriate for equality education learners in CLC. Research Method - The research used a modified Borg and Gall Research and Development (R&D) model, consisting of nine stages: preliminary study, planning, initial product development, expert validation, limited trial, first product revision, large-scale trial, second product revision, and dissemination. The research subjects were equality education learners from three PKBM in West Bandung Regency. Research Findings - The findings show that learners’ productive digital literacy skills were initially low, particularly in content evaluation, knowledge construction, and digital content creation. The developed PjBL model was validated as highly feasible (average score of 82.7%). Model implementation demonstrated good adherence to the PjBL syntax (85.2%) and positive responses from both learners and tutors (85.3%). The large-scale trial showed a 25.4% improvement in digital literacy, with N-Gain values categorized as moderate to high. Research Conclusion - The PjBL-based training model effectively enhances the productive digital literacy skills of PKBM learners, promoting active learning and digital creativity in non-formal education settings. Research Novelty/Contribution - This study contributes theoretically by integrating the PjBL framework into digital literacy training within non-formal education, and practically by offering an applicable model for PKBM institutions, policymakers, and community educators to improve digital empowerment programs.